Evaluating water productivity by tracking the elements of paddy field water balance - Kamal, Md Rowshon; Mojid, Md Abdul; Mousumi, Khadiza Akter; Iqbal, Mazhar (American Society of Civil Engineers (ASCE), 2025)
Real-time adequate water supply is crucial for increasing water productivity (WP) by achieving higher rice yields with less water. Water management, based on productivity parameters, is essential to improve irrigation water use in inefficient irrigation schemes where excessive amounts of water are consumed. This study provides important insights in this regard by experimentally evaluating the water productivity indices (WPI) through intensive monitoring of a paddy field's water balance components during two consecutive rice-growing seasons in 2022 (January to April: first season, and July to October: second season). Water supply and drainage were recorded every minute using a CR200X data logger and MJK 7060 level sensor. Field water depth and rainfall were recorded every 10 min using an 1120 Data-Logging Rain Gauge. Daily crop evapotranspiration (ETc), and seepage and percolation (S&P) were measured with evapotranspiration (ET)-gauges, field lysimeters, and Marriott tube lysimeters. In the first season, the total water requirement for rice was 651 mm, with 448 mm (69%) lost to evaporation, 165 mm (25%) to transpiration, and 38 mm (6%) to S&P. For the second season, the corresponding water components were 604 mm, 406 mm (67%), 146 mm (24%), and 52 mm (9%). Rice yields were 5.5 t/ha in the first season and 6.0 t/ha in the second season. The WPI varied between the two crop seasons having different rainfall patterns. By responding to ETc, S&P, and rainfall fluctuations, farmers can optimize field off-takes to better use rainfall. The real-time monitoring of water balance components can ensure timely and adequate water supply, enhancing water productivity and allowing irrigation managers to plan effectively for improved water and food security.